GAMBARAN VISUM ET REPERTUM PERLUKAAN DI RUMAH SAKIT UMUM DAERAH KUANTAN SINGINGI PERIODE 1 JANUARI 2009 - 31 DESEMBER 2013 - Wilda Septi Pratiwi; Dedi Afandi; Huriatul Masdar (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTVisum et Repertum (VeR) of injury is the type of VeR that most often requested by the investigator to a doctor who works in an emergency room. VeR requested by the investigator is required for law enforcement and justice, so that the quality of VeR which made by a general practitioner affect the clarity of a criminal case and also has a big influence for hospital accreditation. This research were done to figure out VeR of injury in Kuantan Singingi General Hospital during 1st January 2009-31st December 2013. A descriptive retrospective research was designed using Herkutanto’s scoring method. All VeR data in Kuantan Singingi General Hospital during 1st January 2009-31st December 2013 that were complete and has been signed by the doctor who did the examination were counted as samples a hundred fifty four VeR data in Kuantan Singingi General Hospital during 1st January 2009-31st December 2013. Were found injury survivors most cases are in the age group 22-40 years old as many as 78 victims (50,7%), mostly male (61,7%). The most frequent violence that were experienced by the victims were blunt violence was 137 VeR (88,9%) with the highest age group 22-40 years old. The preliminary unit of VeR about 72,3% showed medium quality, the reporting unit about 44,09% showed poor quality and also the inference unit about 40% showed poor quality. It can be concluded that quality of VeR reports in Kuantan Singingi General Hospital during 1st January 2009-31st December 2013 was 43,79% which means poor quality.Keywords: Visum et Repertum, injury, the figure of Visum et Repertum of injury